2014
DOI: 10.1140/epje/i2014-14097-x
|View full text |Cite
|
Sign up to set email alerts
|

Rain water transport and storage in a model sandy soil with hydrogel particle additives

Abstract: We study rain water infiltration and drainage in a dry model sandy soil with superabsorbent hydrogel particle additives by measuring the mass of retained water for non-ponding rainfall using a self-built 3D laboratory set-up. In the pure model sandy soil, the retained water curve measurements indicate that instead of a stable horizontal wetting front that grows downward uniformly, a narrow fingered flow forms under the top layer of water-saturated soil. This rain water channelization phenomenon not only furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The very poor water storage and excessive drainage of control soil, observed in this study, might be due to the preferential flow paths (Annaka and Hanayama, 2010;Yang et al, 2015). In such soils, water wets only a thin surface layer, after which the wetting front grows, penetrates the soil and creates water channel, leading to excessive drainage and low soil water storage (Wei and Durian, 2014;Yang et al, 2015). However, in SAPsamended soil, the PPW decreased and the reduction depended on SAP type, SAP concentration and water application rate.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The very poor water storage and excessive drainage of control soil, observed in this study, might be due to the preferential flow paths (Annaka and Hanayama, 2010;Yang et al, 2015). In such soils, water wets only a thin surface layer, after which the wetting front grows, penetrates the soil and creates water channel, leading to excessive drainage and low soil water storage (Wei and Durian, 2014;Yang et al, 2015). However, in SAPsamended soil, the PPW decreased and the reduction depended on SAP type, SAP concentration and water application rate.…”
Section: Discussionmentioning
confidence: 60%
“…The formation of fingered flows in dry sandy soils, has been shown in several studies (Annaka and Hanayama, 2010;Tullis and Wright, 2007). This phenomenon increases water percolation and markedly reduces water storage in the plant root zone (Wei and Durian, 2014). In rainfed agriculture, due to the poor water retention of light soils and seasonality of rainfall, a significant portion of water is lost via percolation and plants might be subjected to water deficit, even if the precipitation is adequate (Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…The mechanism can be modelled on the basis of the same physical processes as for silica particles with two differences: (i) the value of the maximum packing fraction and (ii) the possibility of water evaporation from the interior of the particles. Equations (9) and (10) are unchanged as the relation between the dry front and the decrease of the drying rate is the same as for silica particles, and particle migration should not differ. Equation 11is modified by adding a third term taking into account the extraction of water from the microgels:…”
Section:    mentioning
confidence: 99%
“…Additives, such as colloids, polymers, hydrogels, and surfactants are used as irrigation water retention agents in soils [2,3,4,5,6] and in mortars, mixed with the pasty material during the preparation [7,8,9]. It is likely that these agents tend to interact and form particulate systems which reduce water mobility [10], but the exact processes of these water retention effects are unclear. In particular, it has been observed that permeability is reduced when such agents are used [11], but there is little information about their exact role.…”
Section: Introductionmentioning
confidence: 99%
“…Water retained by the absorbents generally ranges between 200 and 500 kg/kg of polymer (Bhardwaj et al, ). Polymers suspended in granular packings are widely used as water retention agents in food industry, during building construction for the curing of building materials, in medicine for tissue engineering and drug delivery applications or in agriculture for soil irrigation (Wei & Durian, ). Gel packs are also widely used in the oil and gas industry to seal either fully or partially water production fractures (Chauveteau et al, ; Elsharafi & Bai, ; Simjoo & Koohi, ).…”
Section: Methodsmentioning
confidence: 99%